Carbon fiber cloth surface treatment method
Through a carbon fiber cloth surface treatment method including a variety of environmentally friendly and efficient components, the problems of environmental pollution and single function of traditional treatment methods are solved, and the bonding strength of the carbon fiber cloth and alkaline magnesium sulfate cement are significantly improved.
Patent Information
- Application Number
- CN202510171890.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing carbon fiber cloth surface treatment methods use strong acids or strong alkalis, which lead to environmental pollution and fiber damage. At the same time, traditional coating materials have problems such as long curing time, unfriendly environment and single functionality.
A carbon fiber cloth surface treatment method is adopted, including preparation, surface pretreatment, roughening treatment, cleaning and polishing areas, drying treatment, preparation and coating of surface treatment agents, curing treatment, curing quality inspection and packaging storage. This method uses silane coupling agent to modify nanosilica, bio-based solvent zein, photoinitiation curing agent, benzophenone, self-healing polymer, nanosilver particles, graphene, polyN-isopropylacrylamide, biodegradation additive polylactic acid and photocatalytic nanoparticle titanium dioxide to prepare environmentally friendly surface treatment agents.
It significantly improves the bonding strength between carbon fiber cloth and alkaline magnesium sulfate cement, extends the service life of the material, improves durability and reliability, and reduces the impact on the environment.
Smart Images

Figure CN119874242A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fiber cloth processing, and in particular relates to a carbon fiber cloth surface processing method. Background Art
[0002] Basic magnesium sulfate cement is a kind of magnesium cement. It is a new type of magnesium cement material obtained by adding appropriate modifiers to magnesium sulfate cement. At present, the most studied objects in magnesium cement are basic magnesium sulfate cement and magnesium oxychloride cement. Magnesium oxychloride cement is easy to absorb moisture and return brine, and the chloride ions contained in it will corrode steel bars, thereby limiting its application. Basic magnesium sulfate cement is environmentally friendly, does not contain chloride ions, and has high strength, so it has a wide range of applications. The fiber polymer external bonding reinforcement concrete structure technology has been widely used in engineering practice due to its technical advantages (high strength, high efficiency, simple construction, high efficacy, no need for large construction tools, less construction site, and basically no increase in the original structure's deadweight and the size of the original components). At present, the research on basic magnesium sulfate cement is mostly focused on the study of basic mechanical properties, and no research has been seen in the field of reinforcement. Basic magnesium sulfate cement has strong bonding and is more convenient to construct. You can try to paste multiple layers of carbon fiber cloth to reinforce concrete beams. Therefore, in order to further improve the bonding effect, a large amount of carbon fiber cloth will be used in this process. In order to improve the reinforcement effect, the carbon fiber cloth needs to be surface treated before construction.
[0003] Although common chemical surface treatment can improve the surface activity of carbon fiber cloth, it often requires the use of strong acid or alkali, which pollutes the environment and may damage the fiber itself during the treatment process. At the same time, traditional carbon fiber cloth coating materials often have problems such as long curing time, environmental unfriendliness, and single functionality. Summary of the invention
[0004] The purpose of the present invention is to provide a method for surface treatment of carbon fiber cloth in order to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention is as follows: a method for surface treatment of carbon fiber cloth, the method comprising the following steps:
[0006] A method for treating the surface of a carbon fiber cloth comprises the following steps:
[0007] S1: Carry out preparation work, ensure that the site is clean and ventilated, and prepare carbon fiber cloth, sandpaper, cleaning agent, brush, deionized water, oven tools and materials suitable for basic magnesium sulfate cement;
[0008] S2: Surface pretreatment: Use a brush to gently remove dust and impurities on the surface of the carbon fiber cloth. Use a cleaning agent to clean the possible oil stains and rinse with deionized water to ensure that the cloth surface is clean to meet the requirements of the basic magnesium sulfate cement.
[0009] S3: Roughening treatment, using 240-mesh sandpaper to slightly polish the surface of the carbon fiber cloth to increase its roughness and enhance the bonding performance with basic magnesium sulfate cement;
[0010] S4: Clean the grinding area, clean the debris with a brush after grinding, and rinse the grinding surface thoroughly with deionized water to ensure that there is no dust and impurities, creating good conditions for the bonding of basic magnesium sulfate cement;
[0011] S5: Drying treatment: Place the cleaned carbon fiber cloth in a ventilated place to dry naturally, or use an oven to dry at low temperature to ensure its dryness when pasting it with basic magnesium sulfate cement;
[0012] S6: Prepare and apply a surface treatment agent. According to the characteristics of basic magnesium sulfate cement, a special surface treatment agent is prepared and evenly applied on the surface of the carbon fiber cloth to avoid bubbles and flow and ensure good bonding with basic magnesium sulfate cement; wherein the surface treatment agent includes:
[0013] 90-110 parts by weight of silane coupling agent modified nano silicon dioxide, 270-330 parts by weight of bio-based solvent corn alcohol, 40-60 parts by weight of photoinitiator curing agent benzophenone, 18-22 parts by weight of self-repairing polymer polyurethane-urea, 9-11 parts by weight of nano silver particles, 13-17 parts by weight of graphene, 8-12 parts by weight of poly-N-isopropylacrylamide, 4-6 parts by weight of biodegradable aid polylactic acid and 4-6 parts by weight of photocatalytic nanoparticle titanium dioxide;
[0014] S7: curing treatment, placing the carbon fiber cloth coated with the surface treatment agent in an oven for curing to enhance its bonding strength;
[0015] S8: Curing quality inspection: after the curing is completed, check whether the surface treatment agent of the carbon fiber cloth is uniform and completely cured. If there are defects, make local repairs or re-coat them in time to ensure the bonding effect with basic magnesium sulfate cement;
[0016] S9: Packaging and storage. After the curing inspection is passed, the carbon fiber cloth shall be packaged and stored in a dry and ventilated environment to avoid moisture and pollution to ensure its stable performance when used to reinforce concrete beams.
[0017] In a preferred embodiment, in step S1, the work surface is polished with 600grit sandpaper, a carbon fiber cloth with a thickness of 0.2mm and a width of 1.2m, 240-grit sandpaper, an environmentally friendly cleaning agent with a pH value of 7-8, a soft brush with a bristle length of 25mm, a deionized water resistivity greater than 10MΩ·cm, a preheating oven temperature set to 100±5°C, and an internal size of at least 1m×1m×1m.
[0018] In a preferred embodiment, in step S2, a soft brush is used to gently brush away dust and fine impurities on the surface of the carbon fiber cloth; stubborn stains are gently polished with 240-grit sandpaper, with uniform force to avoid damaging the fibers; an environmentally friendly cleaning agent is diluted in a ratio of 1:10, and the surface is wiped with a soft cloth dipped in the solution to ensure that all oil stains and residues are removed.
[0019] In a preferred embodiment, in step S3, the cleaned carbon fiber cloth is naturally dried or placed in a 60±5°C oven for drying for no less than 30 minutes to remove moisture and solvent vapor. The cleaned carbon fiber cloth is naturally dried or placed in a 60±5°C oven for drying for no less than 30 minutes to remove moisture and solvent vapor.
[0020] In a preferred embodiment, in the step S4, an epoxy resin surface treatment agent with good compatibility with carbon fiber is selected, with a viscosity of 2000-3000cps and a temperature of 25°C; it is evenly applied with a brush, with a coating thickness of 0.01-0.02mm, ensuring that the entire surface of the carbon fiber cloth is covered. An epoxy resin surface treatment agent with good compatibility with carbon fiber is selected, with a viscosity of 2000-3000cps and a temperature of 25°C; it is evenly applied with a brush, with a coating thickness of 0.01-0.02mm, ensuring that the entire surface of the carbon fiber cloth is covered.
[0021] In a preferred embodiment, in step S5, the carbon fiber cloth coated with the surface treatment agent is placed in an oven at 80±5°C for a curing time of 60±10 minutes to ensure that the treatment agent is completely cured.
[0022] In a preferred embodiment, in step S6, the method for preparing the surface treatment agent comprises:
[0023] Nano-silica modified with a silane coupling agent is mixed with the bio-based solvent corn alcohol to form a basic suspension, and then a photoinitiator curing agent, a self-healing polymer, nano-silver particles, graphene, poly (N-isopropylacrylamide), a biodegradable aid and photocatalytic nanoparticles are gradually added; stirring and ultrasonic treatment are used to ensure that the ingredients are evenly dispersed, and finally the curing reaction is initiated by light or heat treatment to prepare a uniform and stable surface treatment agent.
[0024] In a preferred embodiment, in step S7, if defects are found, a small brush is used to dip an appropriate amount of surface treatment agent for repair; after repair, the product is put back into the oven and cured under the same curing conditions, and the curing time can be shortened to 30 minutes. If defects are found, a small brush is used to dip an appropriate amount of surface treatment agent for repair; after repair, the product is put back into the oven and cured under the same curing conditions, and the curing time can be shortened to 30 minutes.
[0025] In a preferred embodiment, in step S8, the inspection should be carried out under good lighting conditions, and it is recommended to use a lighting source with a color temperature of 6500K to accurately evaluate the color and uniformity of the cured layer; the inspector needs to wear clean white gloves and gently touch the cured surface to feel whether there are uneven or sticky areas; at the same time, use a magnifying glass or microscope to carefully observe the surface to check whether there are tiny cracks, bubbles or uncured spots; for any defects found, it is necessary to record their location and nature, and decide whether they need to be repaired again; if the surface treatment agent is uniform, defect-free, and completely cured, the next step of packaging and storage can be carried out; in addition, the physical properties of the carbon fiber cloth, such as flexibility, tensile strength, etc., need to be checked to ensure that the processing process has no adverse effects on it.
[0026] In a preferred embodiment, in step S9, after the curing inspection is passed, the carbon fiber cloth is wound on a clean plastic or paper tube, and the outer layer is sealed with a moisture-proof and dust-proof plastic bag; the relative humidity of the storage environment is 40-60%, and the temperature is 15-30°C; the storage area is regularly inspected to ensure that the environmental temperature and humidity are stable and to avoid direct sunlight and mechanical damage.
[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0028] 1. In the present invention, by adopting silane coupling agent modified nano silicon dioxide, the bonding strength between carbon fiber cloth and basic magnesium sulfate cement matrix material is significantly improved. The addition of this modified nano silicon dioxide not only strengthens the chemical bonding force of carbon fiber cloth and basic magnesium sulfate cement interface, but also improves the surface activity through the modification of silane coupling agent, so that the application of carbon fiber cloth in basic magnesium sulfate cement composite material is more extensive and reliable. In addition, the use of bio-based solvent corn alcohol not only reduces the emission of volatile organic compounds, maintains excellent solubility, contributes to the uniform dispersion of each component on the surface of basic magnesium sulfate cement, and the introduction of light-triggered curing agent benzophenone ensures that the surface treatment agent is rapidly cured under illumination conditions, and improves the production efficiency of supporting use with basic magnesium sulfate cement.
[0029] 2. In the present invention, the repair polymer polyurethane-urea introduced gives the carbon fiber cloth the ability to self-repair during the pasting process of magnesium sulfate cement, thereby extending the service life of the material in concrete beam reinforcement and improving its durability and reliability in complex environments. The addition of nanosilver particles and graphene not only enhances the electrical conductivity and thermal conductivity of the carbon fiber cloth, provides excellent antibacterial properties for magnesium sulfate cement, but also improves the comprehensive performance of the overall material. The addition of poly-N-isopropylacrylamide and biodegradable agent polylactic acid makes the surface treatment agent more environmentally friendly and reduces the impact on the environment. Finally, the photocatalytic performance of photocatalytic nanoparticles titanium dioxide helps to decompose stains on the surface of magnesium sulfate cement and keep the material clean for a long time. Therefore, the surface treatment method of the present invention not only significantly improves the performance of carbon fiber cloth in magnesium sulfate cement reinforced concrete beams, but also fully considers environmental protection and sustainability, bringing significant comprehensive benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the process principle of the present invention;
[0031] Figure 2 Load-deflection curves of specimens reinforced with different carbon fiber cloths. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] Embodiment 1:
[0034] Reference Figure 1 , a carbon fiber cloth surface treatment method, the method comprising the following steps:
[0035] S1: Carry out preparation work, ensure that the site is clean and ventilated, and prepare carbon fiber cloth, sandpaper, cleaning agent, brush, deionized water, oven tools and materials suitable for basic magnesium sulfate cement;
[0036] S2: Surface pretreatment: Use a brush to gently remove dust and impurities on the surface of the carbon fiber cloth. Use a cleaning agent to clean the possible oil stains and rinse with deionized water to ensure that the cloth surface is clean to meet the requirements of the basic magnesium sulfate cement.
[0037] S3: Roughening treatment, using 240-mesh sandpaper to slightly polish the surface of the carbon fiber cloth to increase its roughness and enhance the bonding performance with basic magnesium sulfate cement;
[0038] S4: Clean the grinding area, clean the debris with a brush after grinding, and rinse the grinding surface thoroughly with deionized water to ensure that there is no dust and impurities, creating good conditions for the bonding of basic magnesium sulfate cement;
[0039] S5: Drying treatment: Place the cleaned carbon fiber cloth in a ventilated place to dry naturally, or use an oven to dry at low temperature to ensure its dryness when pasting it with basic magnesium sulfate cement;
[0040] S6: Prepare and apply a surface treatment agent. According to the characteristics of basic magnesium sulfate cement, a special surface treatment agent is prepared and evenly applied on the surface of the carbon fiber cloth to avoid bubbles and flow, and ensure good bonding with basic magnesium sulfate cement; 90 parts by weight of silane coupling agent modified nano-silicon dioxide, 270 parts by weight of bio-based solvent corn alcohol, 40 parts by weight of photoinitiator curing agent benzophenone, 18 parts by weight of self-repairing polymer polyurethane-urea, 9 parts by weight of nano-silver particles, 13 parts by weight of graphene, 8 parts by weight of poly-N-isopropylacrylamide, 4 parts by weight of biodegradable aid polylactic acid, and 4 parts by weight of photocatalytic nano-particles of titanium dioxide;
[0041] S7: curing treatment, placing the carbon fiber cloth coated with the surface treatment agent in an oven for curing to enhance its bonding strength;
[0042] S8: Curing quality inspection: after the curing is completed, check whether the surface treatment agent of the carbon fiber cloth is uniform and completely cured. If there are defects, make local repairs or re-coat them in time to ensure the bonding effect with basic magnesium sulfate cement;
[0043] S9: Packaging and storage. After the curing inspection is passed, the carbon fiber cloth shall be packaged and stored in a dry and ventilated environment to avoid moisture and pollution to ensure its stable performance when used to reinforce concrete beams.
[0044] In step S1, the work surface is polished with 600grit sandpaper, a carbon fiber cloth with a thickness of 0.2 mm and a width of 1.2 m, 240-grit sandpaper, an environmentally friendly cleaning agent with a pH value of 7-8, a soft brush with a bristle length of 25 mm, a deionized water resistivity greater than 10 MΩ·cm, a preheating oven temperature set at 100±5°C, and an internal size of at least 1 m×1 m×1 m.
[0045] In step S2, use a soft brush to gently brush away dust and fine impurities on the surface of the carbon fiber cloth. Stubborn stains are gently polished with 240-grit sandpaper, and the force is even to avoid damaging the fiber. Use an environmentally friendly cleaning agent diluted in a ratio of 1:10, and wipe the surface with a soft cloth dipped in the solution to ensure that all oil stains and residues are removed.
[0046] In step S3, the cleaned carbon fiber cloth is naturally dried or placed in a 60±5°C oven for drying for no less than 30 minutes to remove moisture and solvent vapor. The cleaned carbon fiber cloth is naturally dried or placed in a 60±5°C oven for drying for no less than 30 minutes to remove moisture and solvent vapor.
[0047] In step S4, an epoxy resin surface treatment agent with good compatibility with carbon fiber is selected, with a viscosity of 2000-3000cps and a temperature of 25°C. The surface is evenly coated with a brush, with a coating thickness of 0.01-0.02mm, ensuring that the entire surface of the carbon fiber cloth is covered. An epoxy resin surface treatment agent with good compatibility with carbon fiber is selected, with a viscosity of 2000-3000cps and a temperature of 25°C. The surface is evenly coated with a brush, with a coating thickness of 0.01-0.02mm, ensuring that the entire surface of the carbon fiber cloth is covered.
[0048] In step S5, the carbon fiber cloth coated with the surface treatment agent is placed in an oven at 80±5°C for a curing time of 60±10 minutes to ensure that the treatment agent is completely cured.
[0049] In step S6, the preparation method of the surface treatment agent includes:
[0050] The nano-silica modified by silane coupling agent is mixed with the bio-based solvent corn alcohol to form a basic suspension, and then the photoinitiator curing agent, self-healing polymer, nano-silver particles, graphene, poly-N-isopropylacrylamide, biodegradation aid and photocatalytic nanoparticles are gradually added. The components are uniformly dispersed by stirring and ultrasonic treatment, and finally the curing reaction is initiated by light or heat treatment to prepare a uniform and stable surface treatment agent.
[0051] In step S7, if defects are found, a small brush is used to dip an appropriate amount of surface treatment agent to repair them. After repair, the surface is put back into the oven and cured under the same curing conditions. The curing time can be shortened to 30 minutes. If defects are found, a small brush is used to dip an appropriate amount of surface treatment agent to repair them. After repair, the surface is put back into the oven and cured under the same curing conditions. The curing time can be shortened to 30 minutes.
[0052] In step S8, the inspection should be carried out under good lighting conditions. It is recommended to use a lighting source with a color temperature of 6500K to accurately evaluate the color and uniformity of the cured layer. The inspector needs to wear clean white gloves and gently touch the cured surface to feel whether there are uneven or sticky areas. At the same time, use a magnifying glass or microscope to carefully observe the surface to check for tiny cracks, bubbles or uncured spots. For any defects found, it is necessary to record their location and nature and decide whether they need to be repaired again. If the surface treatment agent is uniform, defect-free, and completely cured, the next step of packaging and storage can be carried out. In addition, the physical properties of the carbon fiber cloth, such as flexibility, tensile strength, etc., need to be checked to ensure that the processing process has no adverse effects on it.
[0053] In step S9, after the curing inspection is qualified, the carbon fiber cloth is wound on a clean plastic or paper tube, and the outer layer is sealed with a moisture-proof and dust-proof plastic bag. The relative humidity of the storage environment is 40-60%, and the temperature is 15-30°C. The storage area is regularly checked to ensure that the ambient temperature and humidity are stable and to avoid direct sunlight and mechanical damage.
[0054] In the present invention, by adopting silane coupling agent modified nano silicon dioxide, it can be known from experimental data that the bonding strength between carbon fiber cloth and basic magnesium sulfate cement matrix material is significantly improved. The addition of this modified nano silicon dioxide not only strengthens the chemical bonding force of carbon fiber cloth and basic magnesium sulfate cement interface, but also improves the surface activity through the modification of silane coupling agent, so that the application of carbon fiber cloth in basic magnesium sulfate cement composite material is more extensive and reliable. In addition, the use of bio-based solvent corn alcohol not only reduces the emission of volatile organic compounds, maintains excellent solubility, and helps the uniform dispersion of each component on the surface of basic magnesium sulfate cement, and the introduction of light-triggered curing agent benzophenone ensures that the surface treatment agent is quickly cured under illumination conditions, and improves the production efficiency of supporting use with basic magnesium sulfate cement.
[0055] In the present invention, the introduced repair polymer polyurethane-urea gives the carbon fiber cloth the ability to self-repair during the pasting process of magnesium sulfate cement, thereby extending the service life of the material in concrete beam reinforcement and improving its durability and reliability in complex environments. The addition of nanosilver particles and graphene not only enhances the electrical conductivity and thermal conductivity of the carbon fiber cloth, provides excellent antibacterial properties for magnesium sulfate cement, but also improves the comprehensive performance of the overall material. The addition of poly-N-isopropylacrylamide and biodegradable agent polylactic acid makes the surface treatment agent more environmentally friendly and reduces the impact on the environment. Finally, the photocatalytic performance of photocatalytic nanoparticles titanium dioxide helps to decompose stains on the surface of magnesium sulfate cement and keep the material clean for a long time. Therefore, the surface treatment method of the present invention not only significantly improves the performance of carbon fiber cloth in magnesium sulfate cement reinforced concrete beams, but also fully considers environmental protection and sustainability, bringing significant comprehensive benefits.
[0056] Embodiment 2:
[0057] Reference Figure 1 , a carbon fiber cloth surface treatment method, the method comprising the following steps:
[0058] S1: Carry out preparation work, ensure that the site is clean and ventilated, and prepare carbon fiber cloth, sandpaper, cleaning agent, brush, deionized water, oven tools and materials suitable for basic magnesium sulfate cement;
[0059] S2: Surface pretreatment: Use a brush to gently remove dust and impurities on the surface of the carbon fiber cloth. Use a cleaning agent to clean the possible oil stains and rinse with deionized water to ensure that the cloth surface is clean to meet the requirements of the basic magnesium sulfate cement.
[0060] S3: Roughening treatment, using 240-mesh sandpaper to slightly polish the surface of the carbon fiber cloth to increase its roughness and enhance the bonding performance with basic magnesium sulfate cement;
[0061] S4: Clean the grinding area, clean the debris with a brush after grinding, and rinse the grinding surface thoroughly with deionized water to ensure that there is no dust and impurities, creating good conditions for the bonding of basic magnesium sulfate cement;
[0062] S5: Drying treatment: Place the cleaned carbon fiber cloth in a ventilated place to dry naturally, or use an oven to dry at low temperature to ensure its dryness when pasting it with basic magnesium sulfate cement;
[0063] S6: Prepare and apply a surface treatment agent. According to the characteristics of basic magnesium sulfate cement, a special surface treatment agent is prepared and evenly applied on the surface of the carbon fiber cloth to avoid bubbles and flow and ensure good bonding with basic magnesium sulfate cement; wherein the surface treatment agent includes:
[0064] 110 parts by weight of silane coupling agent modified nano-silicon dioxide, 330 parts by weight of bio-based solvent corn alcohol, 60 parts by weight of photoinitiator curing agent benzophenone, 22 parts by weight of self-repairing polymer polyurethane-urea, 11 parts by weight of nano-silver particles, 17 parts by weight of graphene, 12 parts by weight of poly-N-isopropylacrylamide, 6 parts by weight of biodegradable aid polylactic acid and 6 parts by weight of photocatalytic nano-particle titanium dioxide;
[0065] S7: curing treatment, placing the carbon fiber cloth coated with the surface treatment agent in an oven for curing to enhance its bonding strength;
[0066] S8: Curing quality inspection: after the curing is completed, check whether the surface treatment agent of the carbon fiber cloth is uniform and completely cured. If there are defects, make local repairs or re-coat them in time to ensure the bonding effect with basic magnesium sulfate cement;
[0067] S9: Packaging and storage. After the curing inspection is passed, the carbon fiber cloth shall be packaged and stored in a dry and ventilated environment to avoid moisture and pollution to ensure its stable performance when used to reinforce concrete beams.
[0068] In step S1, the work surface is polished with 600grit sandpaper, a carbon fiber cloth with a thickness of 0.2 mm and a width of 1.2 m, 240-grit sandpaper, an environmentally friendly cleaning agent with a pH value of 7-8, a soft brush with a bristle length of 25 mm, a deionized water resistivity greater than 10 MΩ·cm, a preheating oven temperature set at 100±5°C, and an internal size of at least 1 m×1 m×1 m.
[0069] In step S2, use a soft brush to gently brush away dust and fine impurities on the surface of the carbon fiber cloth. Stubborn stains are gently polished with 240-grit sandpaper, and the force is even to avoid damaging the fiber. Use an environmentally friendly cleaning agent diluted in a ratio of 1:10, and wipe the surface with a soft cloth dipped in the solution to ensure that all oil stains and residues are removed.
[0070] In step S3, the cleaned carbon fiber cloth is naturally dried or placed in a 60±5°C oven for drying for no less than 30 minutes to remove moisture and solvent vapor. The cleaned carbon fiber cloth is naturally dried or placed in a 60±5°C oven for drying for no less than 30 minutes to remove moisture and solvent vapor.
[0071] In step S4, an epoxy resin surface treatment agent with good compatibility with carbon fiber is selected, with a viscosity of 2000-3000cps and a temperature of 25°C. The surface is evenly coated with a brush, with a coating thickness of 0.01-0.02mm, ensuring that the entire surface of the carbon fiber cloth is covered. An epoxy resin surface treatment agent with good compatibility with carbon fiber is selected, with a viscosity of 2000-3000cps and a temperature of 25°C. The surface is evenly coated with a brush, with a coating thickness of 0.01-0.02mm, ensuring that the entire surface of the carbon fiber cloth is covered.
[0072] In step S5, the carbon fiber cloth coated with the surface treatment agent is placed in an oven at 80±5°C for a curing time of 60±10 minutes to ensure that the treatment agent is completely cured.
[0073] In step S6, the preparation method of the surface treatment agent includes:
[0074] The nano-silica modified by silane coupling agent is mixed with the bio-based solvent corn alcohol to form a basic suspension, and then the photoinitiator curing agent, self-healing polymer, nano-silver particles, graphene, poly-N-isopropylacrylamide, biodegradation aid and photocatalytic nanoparticles are gradually added. The components are uniformly dispersed by stirring and ultrasonic treatment, and finally the curing reaction is initiated by light or heat treatment to prepare a uniform and stable surface treatment agent.
[0075] In step S7, if defects are found, a small brush is used to dip an appropriate amount of surface treatment agent to repair them. After repair, the surface is put back into the oven and cured under the same curing conditions. The curing time can be shortened to 30 minutes. If defects are found, a small brush is used to dip an appropriate amount of surface treatment agent to repair them. After repair, the surface is put back into the oven and cured under the same curing conditions. The curing time can be shortened to 30 minutes.
[0076] In step S8, the inspection should be carried out under good lighting conditions. It is recommended to use a lighting source with a color temperature of 6500K to accurately evaluate the color and uniformity of the cured layer. The inspector needs to wear clean white gloves and gently touch the cured surface to feel whether there are uneven or sticky areas. At the same time, use a magnifying glass or microscope to carefully observe the surface to check for tiny cracks, bubbles or uncured spots. For any defects found, it is necessary to record their location and nature and decide whether they need to be repaired again. If the surface treatment agent is uniform, defect-free, and completely cured, the next step of packaging and storage can be carried out. In addition, the physical properties of the carbon fiber cloth, such as flexibility, tensile strength, etc., need to be checked to ensure that the processing process has no adverse effects on it.
[0077] In step S9, after the curing inspection is qualified, the carbon fiber cloth is wound on a clean plastic or paper tube, and the outer layer is sealed with a moisture-proof and dust-proof plastic bag. The relative humidity of the storage environment is 40-60%, and the temperature is 15-30°C. The storage area is regularly checked to ensure that the ambient temperature and humidity are stable and to avoid direct sunlight and mechanical damage.
[0078] To further verify the effect of the present invention, the carbon fiber cloth pretreated by the above method and the untreated carbon fiber cloth were respectively compounded with basic magnesium sulfate cement to form a 100mm×100mm×10mm test piece, wherein the molar ratio of MgO / MgSO4 / H2O in the basic magnesium sulfate cement was 9 / 1 / 20, and the carbon fiber cloth was arranged in two layers at 3mm and 5mm from the bottom of the test piece. After demoulding, the test piece was cured for 28 days under natural conditions indoors for a bending test.
[0079] The load-deflection curves of the pretreated carbon fiber cloth and the untreated carbon fiber cloth reinforced specimens are shown in Figure 2 shown.
[0080] according to Figure 2 Compared with untreated carbon fiber cloth, the use of pretreated carbon fiber cloth reinforcement can significantly increase the deflection deformation of the specimen before fracture, which is very helpful to improve the toughness of the specimen. The bending strength of the specimen reinforced with untreated carbon fiber cloth is 11.6Mpa, and the bending strength of the specimen reinforced with pretreated carbon fiber cloth is 14.8Mpa, which is an increase of 28%.
[0081] It can be known from the above that: in the present invention, by adopting silane coupling agent modified nano silicon dioxide, the bonding strength between carbon fiber cloth and basic magnesium sulfate cement matrix material is significantly improved. The addition of this modified nano silicon dioxide not only strengthens the chemical bonding force of carbon fiber cloth and basic magnesium sulfate cement interface, but also improves the surface activity through the modification of silane coupling agent, so that the application of carbon fiber cloth in basic magnesium sulfate cement composite material is more extensive and reliable. In addition, the use of bio-based solvent corn alcohol not only reduces the emission of volatile organic compounds, maintains excellent solubility, and helps the uniform dispersion of each component on the surface of basic magnesium sulfate cement, and the introduction of light-triggered curing agent benzophenone ensures that the surface treatment agent is quickly cured under illumination conditions, and improves the production efficiency of supporting use with basic magnesium sulfate cement.
[0082] In the present invention, the introduced repair polymer polyurethane-urea gives the carbon fiber cloth the ability to self-repair during the pasting process of magnesium sulfate cement, thereby extending the service life of the material in concrete beam reinforcement and improving its durability and reliability in complex environments. The addition of nanosilver particles and graphene not only enhances the electrical conductivity and thermal conductivity of the carbon fiber cloth, provides excellent antibacterial properties for magnesium sulfate cement, but also improves the comprehensive performance of the overall material. The addition of poly-N-isopropylacrylamide and biodegradable agent polylactic acid makes the surface treatment agent more environmentally friendly and reduces the impact on the environment. Finally, the photocatalytic performance of photocatalytic nanoparticles titanium dioxide helps to decompose stains on the surface of magnesium sulfate cement and keep the material clean for a long time. Therefore, the surface treatment method of the present invention not only significantly improves the performance of carbon fiber cloth in magnesium sulfate cement reinforced concrete beams, but also fully considers environmental protection and sustainability, bringing significant comprehensive benefits.
[0083] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for surface treatment of carbon fiber cloth, characterized in that: The following steps are involved: S1: Carry out preparation work, ensure that the site is clean and ventilated, and prepare carbon fiber cloth, sandpaper, cleaning agent, brush, deionized water, oven tools and materials suitable for basic magnesium sulfate cement; S2: Surface pretreatment: Use a brush to gently remove dust and impurities on the surface of the carbon fiber cloth. Use a cleaning agent to clean the possible oil stains and rinse with deionized water to ensure that the cloth surface is clean to meet the requirements of the basic magnesium sulfate cement. S3: Roughening treatment, using 240-mesh sandpaper to slightly polish the surface of the carbon fiber cloth to increase its roughness and enhance the bonding performance with basic magnesium sulfate cement; S4: Clean the grinding area, clean the debris with a brush after grinding, and rinse the grinding surface thoroughly with deionized water to ensure that there is no dust and impurities, creating good conditions for the bonding of basic magnesium sulfate cement; S5: Drying treatment: Place the cleaned carbon fiber cloth in a ventilated place to dry naturally, or use an oven to dry at low temperature to ensure its dryness when pasting it with basic magnesium sulfate cement; S6: Prepare and apply a surface treatment agent. According to the characteristics of basic magnesium sulfate cement, a special surface treatment agent is prepared and evenly applied on the surface of the carbon fiber cloth to avoid bubbles and flow, and ensure good bonding with basic magnesium sulfate cement; The surface treatment agents include: 90-110 parts by weight of silane coupling agent modified nano silicon dioxide, 270-330 parts by weight of bio-based solvent corn alcohol, 40-60 parts by weight of photoinitiator curing agent benzophenone, 18-22 parts by weight of self-repairing polymer polyurethane-urea, 9-11 parts by weight of nano silver particles, 13-17 parts by weight of graphene, 8-12 parts by weight of poly-N-isopropylacrylamide, 4-6 parts by weight of biodegradable aid polylactic acid and 4-6 parts by weight of photocatalytic nanoparticle titanium dioxide; S7: curing treatment, placing the carbon fiber cloth coated with the surface treatment agent in an oven for curing to enhance its bonding strength; S8: Curing quality inspection: after the curing is completed, check whether the surface treatment agent of the carbon fiber cloth is uniform and completely cured. If there are defects, make local repairs or re-coat them in time to ensure the bonding effect with basic magnesium sulfate cement; S9: Packaging and storage. After the curing inspection is passed, the carbon fiber cloth shall be packaged and stored in a dry and ventilated environment to avoid moisture and pollution to ensure its stable performance when used to reinforce concrete beams.
2. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In step S1, the work surface is polished with 600grit sandpaper, a carbon fiber cloth with a thickness of 0.2mm and a width of 1.2m, 240-grit sandpaper, an environmentally friendly cleaning agent with a pH value of 7-8, a soft brush with a bristle length of 25mm, a deionized water resistivity greater than 10MΩ·cm, a preheating oven temperature set at 100±5°C, and an internal size of at least 1m×1m×1m.
3. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In step S2, a soft brush is used to gently brush away dust and fine impurities on the surface of the carbon fiber cloth; stubborn stains are gently polished with 240-grit sandpaper, with uniform force to avoid damaging the fibers; an environmentally friendly cleaning agent is diluted in a ratio of 1:10, and the surface is wiped with a soft cloth dipped in the solution to ensure that all oil stains and residues are removed.
4. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In the step S3, the cleaned carbon fiber cloth is naturally dried or placed in a 60±5°C oven for drying for no less than 30 minutes to remove moisture and solvent vapor. The cleaned carbon fiber cloth is naturally dried or placed in a 60±5°C oven for drying for no less than 30 minutes to remove moisture and solvent vapor.
5. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In the step S4, an epoxy resin surface treatment agent with good compatibility with carbon fiber is selected, with a viscosity of 2000-3000cps and a temperature of 25°C; the surface treatment agent is evenly applied with a brush, with a coating thickness of 0.01-0.02mm, ensuring that the entire surface of the carbon fiber cloth is covered. An epoxy resin surface treatment agent with good compatibility with carbon fiber is selected, with a viscosity of 2000-3000cps and a temperature of 25°C; the surface treatment agent is evenly applied with a brush, with a coating thickness of 0.01-0.02mm, ensuring that the entire surface of the carbon fiber cloth is covered.
6. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In the step S5, the carbon fiber cloth coated with the surface treatment agent is placed in an oven at 80±5°C for a curing time of 60±10 minutes to ensure that the treatment agent is completely cured.
7. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In step S6, the preparation method of the surface treatment agent includes: Nano-silica modified with a silane coupling agent is mixed with the bio-based solvent corn alcohol to form a basic suspension, and then a photoinitiator curing agent, a self-healing polymer, nano-silver particles, graphene, poly (N-isopropylacrylamide), a biodegradable aid and photocatalytic nanoparticles are gradually added; stirring and ultrasonic treatment are used to ensure that the ingredients are evenly dispersed, and finally the curing reaction is initiated by light or heat treatment to prepare a uniform and stable surface treatment agent.
8. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In the step S7, if defects are found, a small brush is used to dip an appropriate amount of surface treatment agent for repair; after repair, the surface is put back into the oven and cured under the same curing conditions. The curing time can be shortened to 30 minutes. If defects are found, a small brush is used to dip an appropriate amount of surface treatment agent for repair; after repair, the surface is put back into the oven and cured under the same curing conditions. The curing time can be shortened to 30 minutes.
9. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In step S8, the inspection should be carried out under good lighting conditions, and it is recommended to use a lighting source with a color temperature of 6500K to accurately evaluate the color and uniformity of the cured layer; the inspector needs to wear clean white gloves and gently touch the cured surface to feel whether there are uneven or sticky areas; at the same time, use a magnifying glass or microscope to carefully observe the surface to check whether there are tiny cracks, bubbles or uncured spots; for any defects found, it is necessary to record their location and nature, and decide whether they need to be repaired again; if the surface treatment agent is uniform, defect-free, and completely cured, the next step of packaging and storage can be carried out; in addition, the physical properties of the carbon fiber cloth, including flexibility and tensile strength, need to be checked to ensure that the processing process has no adverse effects on it.
10. A method for surface treatment of carbon fiber cloth according to claim 1, characterized in that: In step S9, after the curing inspection is passed, the carbon fiber cloth is wound on a clean plastic or paper tube, and the outer layer is sealed with a moisture-proof and dust-proof plastic bag; the relative humidity of the storage environment is 40-60%, and the temperature is 15-30° C. The storage area is regularly inspected to ensure that the environmental temperature and humidity are stable and to avoid direct sunlight and mechanical damage.
Citation Information
Cited By
Gradient curing and bonding method for ceramic matrix composite tensile sample reinforcing sheet
CN121026720A